The Effect of Family Behaviors and Attitudinal Familism on Youth Externalizing Behaviors: Testing for Gene-Environment Interactions with a Twin Design - Angel Trevino; Jinni Su; José M. Causadias; Kathryn Lemery-Chalfant (OSF Registries, 2022)
Childhood externalizing behaviors represent a cluster of behavioral problems consisting of aggressive, hyperactive, and/or disruptive actions (Hinshaw, 1987). Childhood externalizing behaviors are developmental precursors to adolescent and adult problem behaviors such as criminal and violent behavior (Betz, 1995; Farrington, 1989; Moffitt, 1993) and substance use (Timmermans et al., 2008; King et al., 2004; Thompson et al., 2011). Understanding the etiology of externalizing behaviors in childhood has important implications for the development of early interventions that can alleviate behavioral problems in childhood and may prevent the emergence of associated adolescent and adult problem behaviors. Both environmental and biological influences drive the development of externalizing behaviors, not just in additive but in multiplicative ways (Lui, 2004). Highlighting this, the family environment serves as an important social context for children that not only predicts the emergence of externalizing behaviors directly (e.g., Ruiz-Hernandez et al., 2019; Stormont, 1998), but also interacts with genetic influences (i.e., gene-environment interaction; GxE) by either exacerbating or attenuating the effect of genetic risk on externalizing behaviors (e.g., Cheung et al., 2014). However, although much focus has been on the behavioral components of family processes (e.g., family conflict, parenting behaviors), less is known about the effect of family attitudes, such as familism (i.e., attitudes regarding how important family is to individuals; Burgess & Locke, 1945; Sabogal et al., 1987) on youth externalizing outcomes. Further, although familism has been extensively studied and found to promote positive outcomes in Hispanic youth (Valdivieso-Mora et al., 2016; Cahill et al., 2021), these familial attitudes may be present in other racial/ethnic populations and potentially confer similar promotive effects (Schwartz, 2007). Thus, the proposed study will investigate how familism and family behaviors are directly associated with offspring externalizing behaviors in late childhood, whether they moderate the influence of genetic influences on externalizing behaviors (i.e., through GxE), and how these patterns of effect vary across racial/ethnic groups.
Keywords: Developmental Psychology; Social and Behavioral Sciences; Psychology